2021
DOI: 10.1039/d1na00511a
|View full text |Cite
|
Sign up to set email alerts
|

Advances in wearable textile-based micro energy storage devices: structuring, application and perspective

Abstract: The continuous expansion of smart microelectronics puts forward higher requirements for energy conversion, mechanical performance, and biocompatibility of micro energy storage devices (MESDs). Unique porosity, superior flexibility and comfortable breathability...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 181 publications
0
16
0
Order By: Relevance
“…48 For example, PSCs have high potential in wearable devices due to the associated facile fabrication, high PCE and low costs. 39,49,50 To date, the technology has already advanced to mini- and standard-sized modules. 19 For instance, Yeo et al 51 reported PCEs in the 8.1–10% range for scalable flexible and rigid modules with an area of 10 cm 2 .…”
Section: Perovskite Solar Cellsmentioning
confidence: 99%
“…48 For example, PSCs have high potential in wearable devices due to the associated facile fabrication, high PCE and low costs. 39,49,50 To date, the technology has already advanced to mini- and standard-sized modules. 19 For instance, Yeo et al 51 reported PCEs in the 8.1–10% range for scalable flexible and rigid modules with an area of 10 cm 2 .…”
Section: Perovskite Solar Cellsmentioning
confidence: 99%
“…Photolithography, also known as ultraviolet (UV) lithography [22] , is one of the most mature patterning technologies for MB fabrication [23] and is based on photochemical reaction and developing processes. Typically, by applying UV light to a photoresist polymer through a photomask pattern, the positive area (covered by the mask) is soluble in the developer solution while the negative area (exposed to UV light) is retained [14,23] .…”
Section: Photolithographymentioning
confidence: 99%
“…Therefore, the use of MOFs as precursors to construct structurally stable and highperformance low-dimensional nanoporous binder-free exible electrodes directly on substrates remains a focus of interest. 23,24 Given the above, in order to overcome the defects of single electrode materials, improve the electrochemical performance of the electrode material, and realize a supercapacitor with high energy density while maintaining high power density, we used carbon cloth as a substrate to convert Co cations into Co nanoparticles by carbonizing the ZIF-67 organic backbone. The Co nanoparticles were embedded uniformly in the carbon backbone to form Co, C, and N self-doped nanosheets, and then Ni(OH) 2 nanoparticles were grown uniformly on the Co-C-N nanosheets by a simple hydrothermal reaction to form Ni(OH) 2 / Co-C-N/CC nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of MOFs as precursors to construct structurally stable and high-performance low-dimensional nanoporous binder-free flexible electrodes directly on substrates remains a focus of interest. 23,24…”
Section: Introductionmentioning
confidence: 99%